Tool path generation for slow tool servo turning of complex optical surfaces. Issue 1 (July 2015) - Wang, Xingsheng; Fu, Xiuqing; Li, Chunlin; Kang, Min
Abstract Slow tool servo (STS) turning is a superior process for machining precision and complicated surfaces that has already gained a wide application especially in optics industry. However, it is lack of systematically study of tool path generation for STS turning of complex surfaces, especially of interpolation among discrete cutting location points. This paper presents a comprehensive tool path generation strategy for STS turning of complex surfaces, including cutting location point optimized planning, trajectory interpolation, and machining simulation. First, cutting contact point discretization and tool geometry compensation were analyzed during cutting location point planning procedure. Second, Hermite segment interpolation used by trajectory interpolation was analyzed, and three position-velocity-time (PVT) entrance parameters algorithms were put forward, i.e., the constant speed method, area method, and the three points method. Third, the machining simulation was carried out to evaluate the performance of the generated tool path. The analysis ofZ -axis motion characteristics indicated that both the area method (c  = 2/3) and three points method can meet the requirements of smooth velocity ofZ -axis when theZ -axis reciprocating frequency is similar to theC -axis rotating frequency. From the viewpoint of acceleration, the three points method is much better than the area method when theZ -axis reciprocating frequency is significantly greater than theC -axis rotary frequency. Finally, a progressive addition lens surface was fabricated to prove the feasibility of the proposed tool path generation method.